O Baú dos Meus Guardados: Imaginários e lembranças das primeiras vivências escolares - Jablonski, Annanda Diléia (2011)
This work is a research about the imaginaries and memories of the first school experiences and aimed to develop a study on the relevance of memory and imaginary as potencies of self-formation. The theoretical focus is founded on studies developed by the Group of Studies and Research about Imaginary, Education, and Memory (GEPIEM), of the Federal University of Pelotas (UFPel). The main subject was the researcher herself, with the following investigation question: which images emerge from the reservoirs of my memory of the first three school years? As a way to answer this question, the researcher looked in her Chest of Saved, all the imagesremembrances and recollections of those experiences. Also contributed to the research, three former colleagues of that time, who acted as eco-evokers of memories. Along the way, it was discovered that the memories of the first three school years become presents as resonances, whose repercussions are part of the process of self-formation of the researcher, personally and professionally. This finding allowed a greater self-knowledge about human and forming issues, mostly, when it comes to ownership of these reservoirs as forming potencies of students, especially in what refers to the first contact with the school institution. Therefore, it s possible to infer that the evocation of memories and the rescue of the imaginary as a reservoir of the initial processes of formation are extremely important to the path of the human being s self-formation. This research evidences, then, that the memory and the imaginary play a fundamental role in self-knowledge and constitute themselves into potencies of self-formation, as it helps to discuss the self-forming images which inhabit the reservoirs of the human imaginary full of individually and socially constructed meanings